The Effects of Regional Trade Agreements on Philippine Export Competitiveness in ASEAN Markets: Regional Trade Agreements on Philippine Export Competitiveness - Yue Tian (Pacific International Journal, 2025)
This study investigates the effects of regional trade agreements (RTAs) on the export competitiveness of the Philippines within ASEAN markets. Using panel data and fixed effects regression analysis, the research examines how RTA participation, along with factors such as tariff rates, non-tariff measures, logistics performance, infrastructure quality, and digital trade readiness, influence sector-level export performance. The findings reveal that participation in RTAs significantly enhances export value, but the impact is conditional on domestic competitiveness factors. Specifically, improved logistics, digital readiness, and infrastructure quality amplify the benefits of RTAs, while high tariffs and non-tariff barriers impede export growth. Cointegration analysis further confirms that these relationships are stable over the long term. The study underscores the need for complementary domestic reforms to fully leverage the advantages of regional economic integration and promote sustainable export growth. The results provide evidence-based insights for policymakers aiming to strengthen the Philippines’ trade position in ASEAN through strategic investment in trade facilitation and competitiveness-enhancing measures.